Rörelsemönster hos varg i Skandinavien - Björk, Julia (SLU/Dept. of Ecology, 2022)
Predators have an important role in ecosystems due to their regulating effect on lower trophic levels, but their presence provokes a lot of different opinions and a great deal of interest about their behaviors and movements. It has been observed that predators’ movement patterns and activity patterns can be affected by e.g., human impact (e.g., forestry, agriculture, infrastructure), seasons, individual traits and population density. The presence of humans does change the predator’s movement patterns and induces avoidant behaviors, while different seasons and sex mostly affects their daily movements. Population density on the other hand, has more effects on their home range size rather than daily movement patterns. The Scandinavian wolf population is still in a recolonizing phase after being completely extinct during the late 1960s’ and due to low immigration of wolves from Finland and Russia the population suffers from inbreeding. Although other countries have studied movement patterns in wolves, the movement patterns of wolves in Scandinavia have not been investigated in detail. The aim of the study was to determine the Scandinavian wolf population’s distance traveled in a day, if there were differences depending on season, social status and sex, and if their movement patterns were affected by inbreeding and the number of neighbouring territories. Data was collected from 24 GPS-collared wolves during 38 study periods with hourly GPS-positioning. A study period is when the transmitter has been programmed to take GPS positions with hourly or half-hour intervals for previous research. The results showed that the average distance traveled for wolves in a day was 17 km and there were differences due to seasons, social status and sex. Inbreeding and number of neighboring territories did not have an impact on the daily distance traveled. The findings showed that there are several factors that do affect the Scandinavian wolves daily distance traveled.